Ta’ṡīr Istirātījiyyah Hilli al-Musykilāt (Problem Solving Strategy) biwasīlah al-Rusūm al-Bayāniyyah fī Tadrīs al-Tarkīb li Talabah al-Madrasah al-Ṡānawiyyah - Hayati, Fauziyah; Arifin, Zainul; Rahmawati, Rahmawati; Ghani, Abdul (Study Program of Arabic Language Teaching, 2026)
This article presents a study on the effectiveness of implementing problem-solving strategies in teaching Arabic syntax using graphical representations. The study was conducted with eighth-grade students at Madrasah Tsanawiyah Tarbiyah Islamiyah Private School (MTsS-TI) Batang Kabung, Padang, who were divided into two groups: a control class and an experimental class. The objectives of this study are to determine: students’ proficiency in learning Arabic syntax before using problem-solving strategies with graphic media; the steps involved in implementing these strategies; and the impact of applying problem-solving strategies with graphic media on students’ proficiency in learning Arabic syntax after using these strategies. The research method employed in this study is an experimental design with a quantitative approach using a field research model. It is a quasi-experimental study with a Non-Equivalent Control Group design. Data collection techniques included tests, interviews, and document analysis. Data analysis used the t-test and SPSS version 27 for homogeneity testing. The results of the study showed a significant change in test scores in the experimental class before and after the implementation of problem-solving strategies in teaching Arabic syntax using graphical representations among eighth-grade students at Madrasah Tsanawiyah Tarbiyah Islamiyah Private School Batang Kabung in Padang. This indicates that this strategy is effectively improving students’ comprehension of the Arabic syllabus.